General policies of food security after the Coronavirus disease (Iraq as a model) (قضايا سياسية, 2024)
Through research, it can be said that public policy is one of the modern sciences that must be given great importance, because of its impact on the country at all political, economic and social levels, and developed countries have been able to build themselves and reach a high level of prosperity and development as a result of their interest in developing policies. General plans, plans, and programs that it follows to implement its projects and goals.Food security is no less important than national or national security. Countries that have achieved food security have been able to achieve self-sufficiency, which has enabled them to satisfy the needs of society, and made them capable not only of exporting food materials and commodities to countries that suffer from a deficit in food security, but they have also been able to exert pressure The decision maker must make decisions that serve his interests.Despite the resources that Iraq possesses, it was unable to achieve security, sufficiency, and stability in society. Rather, it was more vulnerable to threats and instability due to internal challenges (desertification, falling water levels, deteriorating agricultural production), and external challenges (the Corona pandemic) (the Russian-Ukrainian conflict). ), which was reflected in one way or another on the social classes, especially the poor classes with no income, despite the decisions taken by the Iraqi government to address the problem of high prices and support groups with limited income, they did not eliminate the threat to food security and it became a heavy burden on the state.